Sire evaluation and effect of various factors on growth performance in males of Tharparkar and Karan fries cattle - AHMAD, TAVSIEF; MAGOTRA, ANKIT; GUPTA, A K; DASH, SHAKTI KANT; MOHSIN, MIR; SHABIR, MIR; HAMADANI, AMBREEN; YADAV, B R (The Indian Journal of Animal Sciences, 2021)
The current study was undertaken with the objective of sire evaluation as well as studying the effect of genetic and non-genetic factors on growth performance in males of Tharparkar and Karan Fries Cattle. Data on body weights of Tharparkar and Karan Fries males born during the period 1994-2012 at ICAR-NDRI, Karnal, were utilized. The overall least squares means of birth weight and weights at one-month interval up to 12 months of age were 26.92±0.24, 35.55±0.22, 45.04±0.28, 57.56±0.40, 70.02±0.51, 82.62±0.66, 95.18±0.80, 105.11±1.55, 108.19±1.15, 114.20±1.15, 120.11±1.09, 130.35±1.11 and 136.91±4.13 kg respectively, in KF males. In TP males, least square means for birth and one-month were 21.34±0.77 and 25.63±0.67 kg, respectively. Effect of month and period of birth was highly significant on all traits except 1 month and 12-months for the former effect. The effects of genetic group and parity were mostly significant on body weights in KF males. Regression on birth weight was highly significant for all the weight traits. Effect of sire and birth-month was highly significant on all traits except one-month weight in KF. In Tharparkar, effect of season was highly significant on birth weight. Growth curves were linear, and deviations of average body weekly weight showed more divergence with increasing age. Growth rates from birth to three-months age in KF and TP males were 320 g/day and 226 g/day. Effect of non-genetic factors indicated the need of further improvement in feeding and management practices for augmenting growth, i.e. body weights especially in calves born to primiparous dams.